Pengaruh Teknologi Zaman Modern Atas Pembentukan Konkret Kehidupan Manusia Dalam Perspektif Filsafat Ilmu - I Kadek Arya Sugianta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
Human life is now side by side with technology. Technology is needed by humans to make their lives easier. Without technology, humans cannot develop their lives rapidly. With this increasingly sophisticated technology, humans are increasingly dependent on existing technology. Because now technology is also the basis of human life. By using descriptive qualitative research methods, this study discusses the thoughts of philosophers in relation to certain cultural phenomena in society. This research focuses on the explanation of the influence of modern technology which has definitely changed the way of life of humans in terms of practical life. The role of science in the development of modern technology is the basis for how to see the formation of life today which tends to be practical, positivistic, individualistic. Human abandonment of something metaphysical has become a new phenomenon that coexists with the birth of modern technology; as a result of scientific progress.Keyword: philosophy of science, qualitative descriptive, modern technology.